The Role of Stakeholders in Empowering Songket Weavers in Pandai Sikek Village, X Koto District, Tanah Datar Regency - Muhammad Irfan; Nora Eka Putri (The Future of Education Journal, 2026)
This study aims to analyze the role of stakeholders in empowering songket weaving artisan in Pandai Sikek Village, X Koto District, Tanah Datar Regency and to identify supporting and inhibiting factors in the empowerment process. The research employed a descriptive qualitative approach using interviews, observation, and documentation studies as data collection techniques. The analysis focuses on four main stakeholders: Pandai Sikek Village Government using role theory by Soekanto (2000), Departement of Manpower and Industry using Mahfud et al. (2015), Departemen of Cooperatives, SMEs and Trade using stakeholder theory by Bryson (2004), and songket artisans using empowerment theory by Ma’ani (2011). The results indicate that stakeholders have implemented various empowerment programs such as digital marketing training, business development assistance, marketing facilitation, and capacity building for artisans. However, implementation remains suboptimal due to limited continous assistence, low digital literacy among artisans, weak independent market acces, limited business capital, and artinsans dependence on capital owners. This study shows that collaboration among stakeholders is an essential factor in achieving sustainable artisan empowermant while preserving Minangkabau songket cultural heritage.